Quality of Sleep and Coexistent Psychopathology Have Significant Impact on Fatigue Burden in Patients With Inflammatory Bowel Disease. Issue 5 (May 2018) - Hashash, Jana G.; Ramos-Rivers, Claudia; Youk, Ada; Chiu, Wai Kan; Duff, Kyle; Regueiro, Miguel; Binion, David G.; Koutroubakis, Ioannis; Vachon, Ashley; Benhayon, David; Dunn, Michael A.; Szigethy, Eva M.
Abstract : Background: Fatigue is common in inflammatory bowel disease (IBD) patients and is associated with factors such as psychopathology, sleep quality, and disease activity. Goal: To investigate the combined role of all the above factors in the burden of fatigue among IBD patients. Study: We conducted an observational study of adult patients enrolled in an IBD clinical research registry at a tertiary care clinic. Fatigue burden was defined by Item 1 of the Short-form IBD Questionnaire (SIBDQ), which is scored on a 7-point Likert scale. Crohn's disease (CD) and ulcerative colitis (UC) disease activity were measured with the Harvey-Bradshaw Index or the UC Activity Index, respectively. Labs were obtained to assess anemia, vitamin deficiencies, and inflammatory markers. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Use of psychotropic medications and narcotics was used as proxy measure of psychopathology and pain. Results: Among 685 IBD patients enrolled in the registry, 631 (238 UC, 393 CD) had a complete SIBDQ. High fatigue burden was found in 57.5% of patients (64.4% CD, 46.2% UC). Fatigue burden was significantly associated with sleep disturbance (PSQI), SIBDQ, and disease activity. CD patients had more fatigue burden than UC patients. Multivariate regression showed that poor quality of life, sleep disturbance, and being on a psychotropic medication are significantly associated with fatigue burden for both UC and CD. Conclusion: Because fatigue is common in IBD patients, these findings suggest that attention to quality of sleep and psychopathology is as important as medical disease management.